Factors influencing the practice of charitable giving in pandemic situations: a preliminary study on Islamic Relief Malaysia (IR Malaysia) donors / Azhana Othman and Muhammad Haris Sharim - Othman, Azhana; Sharim, Muhammad Haris (Center for Islamic Philantrophy & Social Finance (CIPSF), 2022)
Malaysian Non-Profit Organizations (NPOs) struggle to raise money because they depend more on individual donations for survival and expansion. Since a number of studies have shown that individuals are a major source of funding for charities, they were chosen as a group of donors. The purpose of this study is to determine the factors that influence charitable giving in Malaysia. The substantive study is based on a sample of sixty-seven Islamic Relief Malaysia (IR Malaysia) donors who participated in online survey in January-December 2021. The survey also requested information from respondents on various criteria of NPO when deciding to donate. Based on the survey, online survey was conducted requesting information on respondents’ demography and psychographic. The results show that older people are more likely to donate, those who are not working also have desire to donate and those who live in urban areas are more likely to donate. As this is a preliminary study, the factors that influence donors will be extended by including related theories.